EFEKTIFITAS FUNGSI PEMBIMBING AKADEMIK DALAM MELAYANI MAHASISWA YANG DIBIMBING (Penelitian pada Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi SurakartaTahun Akademik 2012/ 2013) - Lydia Ersta Kusumaningtyas, AR Koesdyantho (UNIVERSITAS SLAMET RIYADI, 2014)
The title of this study is EFFECTIVENESS OF THE ACADEMIC ADVISOR IN SERVE GUIDED STUDENT (Research on Study Program Counseling and Guidance Faculty of Teacher Training and Education, Slamet Riyadi University Surakarta, Academic Year 2012/2013), This study aims at determining the effectiveness of academic advisor functions in serving guided student.This research is descriptive qualitative. The data is collected by using a questionnaire, while the analysis process of the data is by using the percentage. Based on the research results and leverage the data, it can be seen that the average of lecture of Counseling and Guidance Faculty of Teachers Training and Education has not implemented the duties of academic advisor efficiency. Most lectures (83, 33%) are considered by students to be ineffective in carrying out its function as Academic Advisor. However, there is one lecture that considered has implemented the duties of academic advisor efficiency. Academic advisor activity that not been effective prevalent both in service to students before classes start, during and after the class held over. Keywords: Function of Academic Advisor, Serving Students